The Dynamics of Engagement in E-Learning Environments: Insights and Strategies for Improvement - Sunarya, Po Abas; Alfiah, Fifit; Sholeh, Oleh; Millah, Shofiyul; Hikam, Ihsan Nuril (Jurnal Manajemen Retail Indonesia (JMARI), 2024)
In the rapidly evolving landscape of education, e-learning has emerged as a pivotal mode of instruction. However, fostering engagement in these digital environments presents unique challenges. This study delves into the dynamics of engagement in e-learning, aiming to unravel the multifaceted factors that influence student participation and to propose effective strategies for improvement from a broad sample of learners with qualitative insights from educators and students. The quantitative aspect utilizes a structured survey to gauge the impact of technological, pedagogical, and personal factors on engagement levels. Concurrently, qualitative data, gathered through interviews and focus groups, offers a nuanced understanding of the experiences and perceptions shaping engagement. The study’s findings reveal a complex interplay of factors, including the quality of digital content, interaction opportunities, feedback mechanisms, and individual learner characteristics. Notably, the research highlights the critical role of personalized learning experiences and the need for robust support systems. The discussion synthesizes these insights, outlining practical strategies for educators and institutions to enhance engagement in e-learning. These strategies encompass the adoption of adaptive learning technologies, fostering collaborative learning communities, and providing targeted support for diverse learner needs. The study contributes to the growing body of knowledge on e-learning, offering valuable guidance for optimizing engagement in these digital learning spaces.